2017
DOI: 10.1097/nna.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Follow-up of a Regional Evidence-based Practice Fellowship Program

Abstract: The outcome improvements continued 6 months after the fellowship program, and strong EBP beliefs predicted EBP adoption in the participants' units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The Iowa Model of Evidence‐Based Practice to Promote Quality Care (Titler et al, 2001) was integrated into the curriculum to assist program scholar's efforts to systematically direct EBP implementation at the organizational level. Additional strategies were incorporated to facilitate comprehensive program engagement, including one‐to‐one mentoring (Kim et al, 2017), institutional recognition, and protected time (Rickard et al, 2009). The academic‐practice partnership between the healthcare organization and university school of nursing enabled the provision of critical joint educational and healthcare institutional support to scholars.…”
Section: Strategymentioning
confidence: 99%
“…The Iowa Model of Evidence‐Based Practice to Promote Quality Care (Titler et al, 2001) was integrated into the curriculum to assist program scholar's efforts to systematically direct EBP implementation at the organizational level. Additional strategies were incorporated to facilitate comprehensive program engagement, including one‐to‐one mentoring (Kim et al, 2017), institutional recognition, and protected time (Rickard et al, 2009). The academic‐practice partnership between the healthcare organization and university school of nursing enabled the provision of critical joint educational and healthcare institutional support to scholars.…”
Section: Strategymentioning
confidence: 99%
“…16,17 Kim et al 18 reported improved job satisfaction and group cohesion at the completion of a 9-month fellowship. Equally important were qualitative outcomes, which included increased professional growth, renewed passion for nursing, increased nursing confidence that practice change can occur, and the desire to pursue graduate school reported by Weeks et al 17 Kim et al 19 examined 6-month postfellowship outcomes and found significant improvements in EBP beliefs, implementation, and group cohesion, which preceded adoption of EBP. However, evaluation of the long-term outcomes of a regional EBP collaborative academicpractice partnership is needed to determine sustained change…”
Section: Introductionmentioning
confidence: 99%